2020
DOI: 10.1097/lgt.0000000000000581
|View full text |Cite
|
Sign up to set email alerts
|

Erosive Vulvar Lichen Planus and Risk of Vulvar Neoplasia

Abstract: Objective The aim of the study was to assess the risk of vulvar cancer and precursors in a cohort of women with vulvar lichen planus (LP) and the clinical and therapeutic features of these patients. Materials and Methods A retrospective cohort study, including all the women with the diagnosis of vulvar LP, followed in one institution during a period of 11 years, was performed. Demographic and clinical data, as well as treatment, follow-up, and histology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…In another study, the diagnosis of VC was preceded by that of dVIN (9/10 cases) and HSIL (1/10 cases) 34 . In yet another publication, the 2 cases of VC that developed during follow-up were preceded by vulvar HSIL 37 . The development of dVIN or VC was systematically associated with severe treatment-resistant disease in one study (2 cases of VC and 1 case of dVIN) 10 …”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…In another study, the diagnosis of VC was preceded by that of dVIN (9/10 cases) and HSIL (1/10 cases) 34 . In yet another publication, the 2 cases of VC that developed during follow-up were preceded by vulvar HSIL 37 . The development of dVIN or VC was systematically associated with severe treatment-resistant disease in one study (2 cases of VC and 1 case of dVIN) 10 …”
Section: Resultsmentioning
confidence: 95%
“…Of the 416 studies initially selected (231 after the exclusion of duplicates), 22 were considered for the analytic synthesis: 14 on VLS 1,15,16,20–30 and 8 on VLP 10,31–37 (see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Lichen sclerosis, lichen planus, and Paget disease of the vulva were associated with vulvar cancer. [35][36][37][38][39][40] These conditions are not thought to involve HPV infection, as is differentiated vulvar intraepithelial neoplasia (VIN), which is associated with incident cancer and progression to vulvar cancer over many years. 41,42 Several studies found that the risk of associated vulvar cancer persisted beyond 5 years after a diagnosis of lichen sclerosis.…”
Section: Other Vulvar Diseasesmentioning
confidence: 99%
“…Yeon et al (4) treated 32 patients with the 2 types of lichen-like lesions of the vulva with a pelvic abdominal dynamic therapeutic apparatus, and reported a total effective rate of 93.8% and a cure rate of 18.8%. Lyra et al (5) treated 50 patients with vulvar lichen-like lesions with a pelvic abdominal dynamic therapeutic apparatus and reported a symptom improvement rate of 100%, and an effective rate of 54%. However, the effectiveness evaluation indicators of these studies were not comprehensive or perfect, and no stratified study has been conducted.…”
Section: Introductionmentioning
confidence: 99%